The Effect of a Remote Network Technology Supervised Exercise Program Combined With Drug Treatment for Fibromyalgia: Randomized, Single-Blind, Controlled Trial - Cuomaoji Zhang; Peijun Zhang; Yuanmeng Zhao; Yuntao Liu; Yun Hu; Zihan Zhu; Hong Xiao (Journal of Medical Internet Research)
Abstract BackgroundFibromyalgia (FM) is a chronic musculoskeletal pain disorder that is seldom reported in China. Recent studies have focused on nondrug treatments, particularly physical therapy, as an alternative to treatments using medication. With the rise of smartphones and mobile communication, mobile health technology has become a significant area of study. ObjectiveThis study aims to explore whether using remote network applications to supervise patient exercise, in combination with medication, can improve FM pain. It builds on previous research that focuses on drug treatments and offers insights into individualized exercise therapy for FM. Methods The study used a prospective, randomized controlled design with 80 participants, who were divided into 2 groups: supervised and unsupervised. Both groups received a drug regimen: oral pregabalin (75‐150 mg twice daily) and duloxetine (30‐60 mg once daily). The supervised group followed exercise routines with guidance from web-based rehabilitation therapist via a remote network application, while the unsupervised group exercised without supervision. The study was blinded to the participants. Primary outcomes were pain levels over the past 24 hours as measured by the Brief Pain Inventory (BPI). Secondary outcomes included pain relief, sleep improvement, quality of life, and adverse event occurrences. Observations were made at the start of treatment (T0), 1 month after treatment (T1), and 3 months after treatment (T3). ResultsWe recruited 80 participants, evenly divided into 2 groups, from August 2022 to December 2023 at West China Hospital of Sichuan University. Comparisons of the 2 groups were performed using analysis of variance and Bonferroni post hoc analyses (SPSS version 25 for Windows, P ConclusionsThe study showed that exercise combined with drug therapy can significantly improve the prognosis of FM, including pain relief, better sleep, and better overall quality of life; long-term supervised exercise training is more effective in improving FM symptoms and is safer and more reliable than unsupervised exercise.